1974
DOI: 10.1071/bi9740441
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Resistance to Desiccation in Populations of Drosophila melanogaster and D. simulans

Abstract: Populations of D. melanogaster and D. simulans from Melbourne, Vic., and Brisbane, Qld, were regularly sampled for resistance to desiccation. D. melanogaster was more resistant than D. simulans and females of each species were more resistant than males for both populations.The resistance observed for the D. melanogaster population from Melbourne and for the populations of both species from Brisbane remained fairly constant throughout a yearly cycle. However, the resistance of the D. simulans population from Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
32
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 30 publications
12
32
0
Order By: Relevance
“…There is also evidence for selection shifting levels of resistance within populations. In particular, McKenzie and Parsons (1974) showed that desiccation resistance varied seasonally in a temperate population of D. simulans, which is consistent with changes in levels of stress likely to be experienced by this population.…”
Section: Ananassae Zaprionus Indianus)supporting
confidence: 49%
See 1 more Smart Citation
“…There is also evidence for selection shifting levels of resistance within populations. In particular, McKenzie and Parsons (1974) showed that desiccation resistance varied seasonally in a temperate population of D. simulans, which is consistent with changes in levels of stress likely to be experienced by this population.…”
Section: Ananassae Zaprionus Indianus)supporting
confidence: 49%
“…There is also evidence for selection shifting levels of resistance within populations. In particular, McKenzie and Parsons (1974) showed that desiccation resistance varied seasonally in a temperate population of D. simulans, which is consistent with changes in levels of stress likely to be experienced by this population.In this paper, we are concerned with patterns of variation in stress resistance traits. The main question we address is as follows: How strong is variation at the local and intrapopulation levels for stress resistance compared to the difference between a temperate and tropical region?…”
supporting
confidence: 49%
“…The dissimilarity between species was in accord with the finding that, there is a general superiority of D. melanogaster over D. simulans in different traits (Palabost, 1972;Marques, 1973;Cordeiro, et al, 1973;McKenzie and Parsons, 1974;Parsons, 1975;Levine et al, 1989;andPimentel et al, 2003, 2004). The difference between species grew as the time of exposure increased (Fig.…”
Section: Comparison Between Collection Sitessupporting
confidence: 86%
“…The effects of desiccation stress on adult Drosophila melanogaster and Drosophila simulans have been compared in the laboratory by McKenzie and Parsons (1974), who found that the former species showed significantly greater survival at 0 % relative humidity than the latter. Kurnell (personal communication), using a similar technique, found that Drosophila immigrans, despite its larger size, was less resistant than either of these species.…”
Section: Introductionmentioning
confidence: 99%